(untitled) (Journal of Surgical Sciences, 2019)
Background: Complete rectal prolapse is a very distressing condition. In adults, the only potentially curative treatment for complete rectal prolapse is surgery either by transabdominal or perinea! approaches. Till date abdominal rectopexy is considered as the standard surgical treatment for complete rectal prolapse, which can be done laparoscopically or by open procedure. Objective: The purpose of the study was to observe the outcome of Laparoscopic rectopexy in the treatment of complete rectal prolapse by subjective assessment and to compare the result with that of conventional open abdominal rectopexy. Methodology: This randomized clinical trial was carried out in the Department of Surgery at Bangabandhu Sheikh Mujib Medical University, Dhaka, from July 2012 to June 2014 for a period of twenty four (24) months. Patients who presented with complete rectal prolapse with age ranging from 25 to 70 years irrespective of gender were selected as study population. Patients were randomized by lottery method into two groups as group I who underwent laparoscopic rectopexy (LR) and group II who underwent open rectopexy (OR). Result: A total number of 50 patients were recruited in this study of which 25 patients were. in group I and 25 patients were in group II. The mean (s.d.) age was 49.40 (13.22) years and 46.48(13.27) years in group I and group II respectively (p>0.05). The mean (s.d.) operative time was 115(19) minutes in group I and 75(12) minutes in group II (p<0.05). In this study 1(4.0%) patient and 6 (24.0%) patients had abdominal wound infection in group I and in group II respectively (p>0.05). Mean (s.d.) ambulation time was 1.96 (0.67) days in group I and 3.92(1.15) days in groups II (p<0.05). Postoperative hospital stay mean (s.d.) was 3.08(1.18) days in group I and 8.16(3.57) days in group II (p<0.05). Overall patients satisfaction were 92% and 76% in group I and group II respectively (p>0.05). Conclusion: Laparoscopic rectopexy is a better option than conventional open abdominal rectopexy for the treatment of complete rectal prolapse. Journal of Surgical Sciences (2015) Vol. 19 (1) : 3-7